2021
DOI: 10.1080/14794802.2021.1897035
|View full text |Cite
|
Sign up to set email alerts
|

Valid and valuable: lower attaining pupils’ contributions to mixed attainment mathematics in primary schools

Abstract: Existing research establishes that lower attaining pupils derive mathematical learning benefit from working in mixed attainment groupings. However, gains for lower attaining pupils are seen to derive from the contributions of higher attaining peers; evidence of the contributions that lower attaining pupils make to mixed attainment activity is currently lacking. This study contributes evidence of the merits of mixed attainment working through its focus on the mathematical contributions of lower attaining primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We argue that rich tasks have the potential to cultivate and encourage learning situations that can be observed within the frames of potential knowledge, actualization, and activity systems [14]. Moreover, extant research has indicated that rich mathematics tasks provide opportunities for all students to contribute mathematically, regardless of previous achievement and gender [5,25].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…We argue that rich tasks have the potential to cultivate and encourage learning situations that can be observed within the frames of potential knowledge, actualization, and activity systems [14]. Moreover, extant research has indicated that rich mathematics tasks provide opportunities for all students to contribute mathematically, regardless of previous achievement and gender [5,25].…”
Section: Theorymentioning
confidence: 99%
“…What is important, in our opinion, is that gifted students are not readily identifiable in the classroom. This point has been underscored in research on low-achieving students, which found that these students contribute sophisticated and abstract mathematical ideas [25,30,32]. Therefore, flexible grouping is important, as it will motivate all gifted students, including those not visible to the teacher, because of low achievement, to participate in collaborative work that seeks to cultivate sophisticated mathematics reasoning.…”
Section: Gifted Students' Collaboration On a Rich Taskmentioning
confidence: 99%
“…were not reaching age related expectations for numeracy skills" (Lane, 2009, p. 152) including children labelled with SEND (Numicon, 2020) for whom their "Breaking Barriers" programme is designed (Teachwire, 2018). Research has suggested that this approach is helpful to both "lower" and "higher" attainers when they work in pairs (Barclay, 2018). This kind of multisensory maths education has been promoted as a way of supporting pupils labelled with SEND or those who have "mathematical difficulties" requiring "individual intervention" (Dowker, 2004;Dowker, 2009) including specifically those with Down's Syndrome (Ewan & Mair, 2002;Faragher, Brady & Gervasoni, 2008;Horner, 2002;Nye, 2006;Nye, Buckley & Bird, 2005, Wing & Tacon, 2007.…”
Section: Numiconmentioning
confidence: 99%